Westonci.ca makes finding answers easy, with a community of experts ready to provide you with the information you seek. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
m in (-oo:+oo)
m+11 = (1/4)*m-(2*m) // - (1/4)*m-(2*m)
m-((1/4)*m)+2*m+11 = 0
m+(-1/4)*m+2*m+11 = 0
11/4*m+11 = 0 // - 11
11/4*m = -11 // : 11/4
m = -11/11/4
m = -4
m = -4
First subtract m over to 11=1/4m-2m-m then factor out an m so 11= m(1/4-2-1) so 11=m(-11/4) then divide over m=-4
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.